2017 IEEE International Conference on Computer Vision Workshops (ICCVW) 2017
DOI: 10.1109/iccvw.2017.254
|View full text |Cite
|
Sign up to set email alerts
|

3D Pose Regression Using Convolutional Neural Networks

Abstract: Abstract3D pose estimation is a key component of many important computer vision tasks such as autonomous navigation and 3D scene understanding. Most state-of-the-art approaches to 3D pose estimation solve this problem as a pose-classification problem in which the pose space is discretized into bins and a CNN classifier is used to predict a pose bin. We argue that the 3D pose space is continuous and propose to solve the pose estimation problem in a CNN regression framework with a suitable representation, data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The pose regression network is structured loosely on the network proposed by [16]. Their network is designed to estimate the pose of an object from a feature vector produced from a pre-trained CNN.…”
Section: Methodsmentioning
confidence: 99%
“…The pose regression network is structured loosely on the network proposed by [16]. Their network is designed to estimate the pose of an object from a feature vector produced from a pre-trained CNN.…”
Section: Methodsmentioning
confidence: 99%
“…The regression ConvNet methodology is also used for predicting stock prices via annual reports and text analysis (Dereli and Saraclar, 2019) and using historical data (Mehtab and Sen, 2020). Other applications include prediction of angles (Fischer et al, 2015), prediction of distances for 3D position estimates (Mahendran et al, 2017), or age estimation (Rothe et al, 2016). In the real estate field, Solovev and Pr€ ollochs (2021) choose a pretrained ConvNet to predict apartment rent prices using pictures of the floor plans as the input.…”
Section: Deep Learning For Visual Pattern Recognitionmentioning
confidence: 99%
“…They developed a CNN regression framework for solving the 3D pose estimation problem in the continuous domain by designing a suitable representation, data augmentation and loss function that respect the non-linear structure of the 3D pose space. 9 Most of the current methods use the Euler angle or quaternion representation to train their networks. 4,9 However, Zhou et al 10 demonstrated that any representation of rotation with four or fewer dimensions is discontinuous and therefore not ideal to use in a learning task for neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…9 Most of the current methods use the Euler angle or quaternion representation to train their networks. 4,9 However, Zhou et al 10 demonstrated that any representation of rotation with four or fewer dimensions is discontinuous and therefore not ideal to use in a learning task for neural networks. They proposed a 6-dimensional rotation representation (6DRep) and proved it is continuously mapped from the rotation space SO(3).…”
Section: Introductionmentioning
confidence: 99%